2017
DOI: 10.3390/molecules22060954
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Complexation of Aptamers by Their Specific Antidotes

Abstract: Nucleic acid ligands, aptamers, harbor the unique characteristics of small molecules and antibodies. The specificity and high affinity of aptamers enable their binding to different targets, such as small molecules, proteins, or cells. Chemical modifications of aptamers allow increased bioavailability. A further great benefit of aptamers is the antidote (AD)-mediated controllability of their effect. In this study, the AD-mediated complexation and neutralization of the thrombin binding aptamer NU172 and Toll-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Furthermore, using a ball coagulometer, slightly higher CTs were also detected in blood samples with 1.0 µM (NU172+ AD) (both time points) than in the control (NaCl), which indicates a remaining amount of NU172 that was not complexed with AD. In accordance with our previous publication [7], already after 5 min of incubation with the AD, the anticoagulation effect of NU172 was abolished and maintained during the dynamic incubation in the in vitro rotation model of 30 min. Figure 7.…”
Section: Analysis Of the Influence Of Nu172 On Coagulation And The Absupporting
confidence: 91%
See 3 more Smart Citations
“…Furthermore, using a ball coagulometer, slightly higher CTs were also detected in blood samples with 1.0 µM (NU172+ AD) (both time points) than in the control (NaCl), which indicates a remaining amount of NU172 that was not complexed with AD. In accordance with our previous publication [7], already after 5 min of incubation with the AD, the anticoagulation effect of NU172 was abolished and maintained during the dynamic incubation in the in vitro rotation model of 30 min. Figure 7.…”
Section: Analysis Of the Influence Of Nu172 On Coagulation And The Absupporting
confidence: 91%
“…In this study, using the new PIEZ system, we were able to reliably measure the coagulation inhibiting effect of the thrombin binding aptamer NU172 after static and dynamic incubation and the ability of its complementary antidote (AD) to abrogate the coagulation inhibitory effect of NU172. In our previous study, the required time for the generation of double-stranded complexes was examined [7], and it was found that the AD was able to bind already after 2 min to the NU172 aptamer, which resulted in rapid abrogation of the anticoagulant activity of NU172 after 5 min in whole blood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The conjugation of polyethylene glycol (PEG) to aptamers delay their renal filtration (Padilla and Sousa, 1999; Sun et al, 2014; Ni et al, 2017; Maio et al, 2018). The pharmacokinetic parameters of an aptamer could be also controlled by an antidote being a complementary oligonucleotide (Oney et al, 2010; Lakhin et al, 2013; Stoll et al, 2017).…”
Section: Introductionmentioning
confidence: 99%